1970
DOI: 10.1042/bj1190757
|View full text |Cite
|
Sign up to set email alerts
|

Creatine regulation in the embryo and growing chick

Abstract: 1. The absence of creatine was demonstrated enzymically in the hen's-egg yolk and in the albumin contrary to former reports. 2. A comparison of the results obtained by enzymic and colorimetric methods to measure creatine is presented. 3. Creatine phosphate was not detected in the yolk extracts. 4. The content of free arginine enzymically assayed was 15.7mumol in the yolk and 3.38mumol in the albumin. Arginine amounts to practically all of the guanidine compounds in the yolk and one-half of those in the albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Reported values of brain PC during chicken embryo development [44], plotted semi logarithmically, do show that extrapolation of the first PC slope to the earliest stage of development supports the idea that brain PC begins to be detected shortly after the 6th day of incubation [39]. This finding fits well with the fact that no PC was present in whole embryo before St 28-29 (day 6 of incubation) [37]. So, any type of catalytical CK present in developing chick tissues before St 28-29, must be considered as non-functional in spite of the availability of creatine since St 23 (day 4 of incubation), in the whole embryo .…”
Section: Brain Ck Strain-specificitysupporting
confidence: 63%
See 2 more Smart Citations
“…Reported values of brain PC during chicken embryo development [44], plotted semi logarithmically, do show that extrapolation of the first PC slope to the earliest stage of development supports the idea that brain PC begins to be detected shortly after the 6th day of incubation [39]. This finding fits well with the fact that no PC was present in whole embryo before St 28-29 (day 6 of incubation) [37]. So, any type of catalytical CK present in developing chick tissues before St 28-29, must be considered as non-functional in spite of the availability of creatine since St 23 (day 4 of incubation), in the whole embryo .…”
Section: Brain Ck Strain-specificitysupporting
confidence: 63%
“…Previously, it has been shown that the earliest chicken CK activity is present in the embryonic heart from 27 h of incubation or about St 8.5 [10]. Also, it has been demonstrated that embryonic heart cannot synthesize creatine [36], and the egg contains neither creatine nor the machinery for its biosynthesis [37]. In fowl, the whole creatine pathway is found in liver [50].…”
Section: Brain Ck Specific Acti6itymentioning
confidence: 99%
See 1 more Smart Citation
“…III). Although the yolk sac of the hen's egg was reported to contain significant amounts of AGAT by Walker (1077), it was suggested not to do so by Ramírez et al (793). Mostly in kidney and pancreas, but also in rat decidua, the levels of AGAT are influenced by a variety of dietary and hormonal factors.…”
Section: A L-arginine:glycine Amidinotransferasementioning
confidence: 99%
“…Indeed, creatine injected into the egg can depress the level of transamidinase. However, Ramirez et al [81] found no evidence for an inverse relationship between endogenous creatine concentration and the level of transamidinase in chick liver.…”
Section: Mechanisms Of Enzyme Formationmentioning
confidence: 99%